Evaluasi Perencanaan Pembangunan Air Minum Melalui Dana Transer ke Daerah - Pambudi, Andi Setyo (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
Drinking water is one of the national development targets of both central and regional governments. Given the importance of the drinking water sector for the community, the local government allocates funding for drinking water through the Local Government Budget mechanism with all of its limitations. One of the central government's supports for drinking water is the transfer of funds to the regions within the scope of the national priority section of the Government Work Plan (GWP). The drinking water development planning is interesting to review from two planning sides: the central government through the Government Work Plan (GWP) and the regional government through the Regional Government Work Plan (RGWP). This study aims at the level of linkage of transfer fund planning related to national priorities, namely the Special Allocation Fund (SAF) for Physical Assignments, in a top-down and bottom-up manner. The method used is a mixed method approach through planning gap analysis based on literature studies on central-regional planning documents and questionnaires. On a more specific side, Central Java Province was chosen as the recipient of the largest SAF allocation in the drinking water sector. The analysis result state that Central Java has not fully allocated a budget for the issue of rural drinking water supply in its regional development planning. The priority for drinking water development in this province has not been stated correctly in the RGWP. Meanwhile, the results of the questionnaire indicated that the implementation of SAF in Central Java which the central government funded was considered to have a positive impact on improving drinking water services and infrastructure as part of the minimum service standard (MSS). The development of drinking water with the SAF budget in Central Java is carried out with good supervision and sufficient funding so that output and realization can occur according to the target. From a planning perspective (gap analysis), the suitability of the SAF menu with the Regional Government Work Plan for drinking water issues is 60 percent.